EDEM2 stably disulfide-bonded to TXNDC11 catalyzes the first mannose trimming step in mammalian glycoprotein ERAD - Ginto George; Satoshi Ninagawa; Hirokazu Yagi; Taiki Saito; Tokiro Ishikawa; Tetsushi Sakuma; Takashi Yamamoto; Koshi Imami; Yasushi Ishihama; Koichi Kato; Tetsuya Okada; Kazutoshi Mori (eLife, 2020)
Sequential mannose trimming of N-glycan (Man9GlcNAc2 -> Man8GlcNAc2 -> Man7GlcNAc2) facilitates endoplasmic reticulum-associated degradation of misfolded glycoproteins (gpERAD). Our gene knockout experiments in human HCT116 cells have revealed that EDEM2 is required for the first step. However, it was previously shown that purified EDEM2 exhibited no α1,2-mannosidase activity toward Man9GlcNAc2 in vitro. Here, we found that EDEM2 was stably disulfide-bonded to TXNDC11, an endoplasmic reticulum protein containing five thioredoxin (Trx)-like domains. C558 present outside of the mannosidase homology domain of EDEM2 was linked to C692 in Trx5, which solely contains the CXXC motif in TXNDC11. This covalent bonding was essential for mannose trimming and subsequent gpERAD in HCT116 cells. Furthermore, EDEM2-TXNDC11 complex purified from transfected HCT116 cells converted Man9GlcNAc2 to Man8GlcNAc2(isomerB) in vitro. Our results establish the role of EDEM2 as an initiator of gpERAD, and represent the first clear demonstration of in vitro mannosidase activity of EDEM family proteins.